2014
DOI: 10.5811/westjem.2013.8.19080
|View full text |Cite
|
Sign up to set email alerts
|

USEFUL: Ultrasound Exam for Underlying Lesions Incorporated into Physical Exam

Abstract: Introduction: The Ultrasound Screening Exam for Underlying Lesions (USEFUL) was developed in an attempt to establish a role for bedside ultrasound in the primary and preventive care setting. It is the purpose of our pilot study to determine if students were first capable of performing all of the various scans required of our USEFUL while defining such an ultrasound-assisted physical exam that would supplement the standard hands-on physical exam in the same head-to-toe structure. We also aimed to assess the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, the careful integration into existing curricula has been demonstrated to enhance physical examination skills by providing real‐time feedback on examination findings . Steller et al demonstrated the feasibility of integrating point‐of‐care US with medical students' physical examinations through the performance of a timed US screening examination for underlying lesions (Kirkpatrick level 2).…”
Section: Educational and Teaching Applicationsmentioning
confidence: 99%
“…However, the careful integration into existing curricula has been demonstrated to enhance physical examination skills by providing real‐time feedback on examination findings . Steller et al demonstrated the feasibility of integrating point‐of‐care US with medical students' physical examinations through the performance of a timed US screening examination for underlying lesions (Kirkpatrick level 2).…”
Section: Educational and Teaching Applicationsmentioning
confidence: 99%
“…The educational interventions found here range from those that teach students to scan a wide range of anatomy [47,48] or regional anatomy [49] to more focused exams of the vascular [50][51][52], abdominal [53][54][55], head and neck [56], cardiac [57,58] and respiratory [59] systems. Some institutions taught students ultrasound-specific protocols such as FAST [60][61][62] or USEFUL [63] scans. Senior medical students, whose learning objectives have graduated to the diagnosing of disease in real-world patients, have demonstrated significant improvement in their ability to diagnose disease following brief, focused ultrasound teaching programs [64][65][66][67][68].…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…rationale for curriculum D2.1 The curriculum prepares students for POCUS (point-of-care ultrasound use) in future clinical work[35,37,38,[67][68][69][70][71][72][73] characteristics of the curriculum D3.1 The ultrasound curriculum forms the foundation for ultrasound training along a continuum of medical education from undergraduate through graduate to continuing medical education[18,19,33,37,38,135,[152][153][154][155] The ultrasound curriculum prepares learners for future additional clinical training and/or practice opportunities[18,19,106,107,135,[152][153][154] 8.14…”
mentioning
confidence: 99%